Sosialisasi Pengenalan Konsep Etnomatematika Pada Siswa Kelas IV SDN 1 Rantepao - Novalia Sulastri; Reni Lolotandung; Weryanti Laen Langi (Nusantara Mengabdi Kepada Negeri, 2025)
The objectives of this Community Service Program are: (1) To introduce the concept of ethnomathematics to students and classroom teachers at UPT SDN 1 Rantepao as a contextual learning approach rooted in local culture, particularly the traditions of the Toraja ethnic group; (2) To enhance students’ understanding and interest in mathematics through the integration of mathematical elements found in Torajan cultural motifs, artifacts, and symbols, such as symmetry, geometric shapes, patterns, and measurement; and (3) To support teachers in developing innovative and meaningful mathematics instruction by connecting mathematical content to real-life contexts that are relevant to students' daily experiences. The program was implemented in five stages: preliminary observation and survey, preparation, implementation, group discussion and reflection, and the final stage—evaluation. Based on the results of the program, the introduction of ethnomathematics based on Torajan local culture successfully contributed to improving students’ mathematical understanding and reinforcing the relevance of mathematics instruction within the local cultural context. The three-day implementation of the program was met with highly positive responses from all school stakeholders, including strong student enthusiasm, active teacher participation, and noticeable changes in instructional practices. Evaluation outcomes demonstrated a significant improvement in student understanding, as reflected by an increase in the average quiz score from 55 to 83. Moreover, the program contributed to social transformation within the school environment, including the formation of culturally based student learning groups, positive shifts in student learning behaviors, the emergence of local student leadership, and increased awareness among both students and teachers of the importance of integrating local cultural values into the learning process.